2020
DOI: 10.1177/1526602820905583
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Gore Excluder Iliac Branch Endoprosthesis Using Division Branches of the Internal Iliac Artery as Distal Landing Zones

Abstract: Purpose: To evaluate the outcomes of the Gore Excluder Iliac Branch Endoprosthesis (IBE) using division branches of the internal iliac artery (IIA) as distal landing zones. Materials and Methods: Between January 1, 2014, and December 31, 2018, 74 patients (mean age 74±7 years; 72 men) treated for aortoiliac or common iliac artery aneurysms had an IBE deployed with distal landing of the side branch within the main trunk (n=60) of the internal iliac artery (IIA) vs within a division branch (n=25). Thirteen (17%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…In case of large hypogastric aneurysms with numerous side branches, others have advocated excluding all of them using coil embolization or vascular plugs since stent oversizing alone may not be sufficient to reliably prevent type 2 endoleaks. 19 Although data in the literature are scarce to assess the long-term clinical relevance of these type 2 endoleaks, some might actually lead to aneurysm sac expansion as also shown in this study, alike to what can be observed after standard or fenestrated-branched EVAR. 20,21 Furthermore, one should consider that embolization of hypogastric side branches when a stent-graft has already been deployed across a hypogastric aneurysm would be an extremely challenging (if not unfeasible) procedure.…”
Section: Discussionsupporting
confidence: 61%
“…In case of large hypogastric aneurysms with numerous side branches, others have advocated excluding all of them using coil embolization or vascular plugs since stent oversizing alone may not be sufficient to reliably prevent type 2 endoleaks. 19 Although data in the literature are scarce to assess the long-term clinical relevance of these type 2 endoleaks, some might actually lead to aneurysm sac expansion as also shown in this study, alike to what can be observed after standard or fenestrated-branched EVAR. 20,21 Furthermore, one should consider that embolization of hypogastric side branches when a stent-graft has already been deployed across a hypogastric aneurysm would be an extremely challenging (if not unfeasible) procedure.…”
Section: Discussionsupporting
confidence: 61%
“…Recent studies are being performed to evaluate distal seals even using division branches of the internal iliac artery, with safe and efficacious results in the midterm. 1 Proximal migration of the iliac limb can lead to type 1b and type 3 endoleaks that may result in abdominal aortic aneurysm (AAA) rupture. 2…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies are being performed to evaluate distal seals even using division branches of the internal iliac artery, with safe and efficacious results in the midterm. 1 Proximal migration of the iliac limb can lead to type 1b and type 3 endoleaks that may result in abdominal aortic aneurysm (AAA) rupture. 2 The presence of common iliac artery (CIA) aneurysm, which does not allow an effective seal, is one of the major anatomic challenges of conventional endovascular aneurysm repair (EVAR).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Cornwall et al 3 treated an IIAA using a Gore IBE with preservation of gluteal perfusion. In addition, D'Oria et al 7 reported that the use of the posterior or anterior division of the IIA as a distal landing zone for the Gore IBE was safe and efficacious in the midterm. In contrast, a few techniques for IIAA repair to preserve the SGA without the use of the Zenith branch graft or Gore IBE have been reported.…”
Section: Discussionmentioning
confidence: 99%